2008
DOI: 10.1021/cg700713g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and First-Principles Studies of Single-Crystalline β-BC2N with Oxygen-Bearing Defects

Abstract: Single-crystalline B-C-N nanorods were prepared at 500 °C and less than about 20 MPa. Results from X-ray powder diffraction (XRD) and selected-area electron diffraction (SAED) measurements suggest that the synthesized single-crystalline B-C-N is of tetragonal structure and its lattice constants are a ) 7.12(5) Å and c ) 3.57(3) Å. The nanorods all are very straight, and the ratios of length to diameter are between 5 and 30. High resolution transmission electron microscopy (HRTEM) and scanning electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Zhao et al [5] successfully synthesized stoichiometric c-BC 2 N and c-BC 4 N crystals with diamondlike structures by using a diamond-anvil cell. Then Fan et al [6][7][8][9][10][11][12][13][14][15] did systematic investigations of these structures based on the first-principles calculations, such as crystal structure, band gap, optical spectrum, ideal strength and hardness, in order to establish facts and reach new conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [5] successfully synthesized stoichiometric c-BC 2 N and c-BC 4 N crystals with diamondlike structures by using a diamond-anvil cell. Then Fan et al [6][7][8][9][10][11][12][13][14][15] did systematic investigations of these structures based on the first-principles calculations, such as crystal structure, band gap, optical spectrum, ideal strength and hardness, in order to establish facts and reach new conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25] Previous studies have reported the synthesis of cubic B-C-N compounds under HPHT conditions. [26][27][28][29][30] A cubic B-C-N phase has been successfully synthesized by Badzian at 14 GPa and 3300 K starting from the graphitic B-C-N, 26 and Kakudate et al 31 have claimed the formation of a cubic B-C-N substance by a shock-wave technique. Knittle et al have also reported the presence of cubic B-C-N both in the microcrystalline B-C-N compounds and the graphite-structured mixture of BN and C as starting materials, prepared at 30 GPa and 1500 K. Moreover, a mixture of diamond, c-BN, and cubic B-C-N substances is produced by Nakano et al under 7.7 GPa in the temperature range from 2420 to 2570 K, but the cubic B-C-N substance tends to decompose into diamond and c-BN at higher temperatures, which suggests that the cubic B-C-N compound is not thermodynamically stable.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the carbon and boron nitride have the same types of polymorphs, such as hexagonal forms (graphite and h-BN) and cubic ones (diamond and c-BN), a cubic B−C−N alloy would be expected to be prepared by transformation from HPHT conditions, by analogy with the preparation of diamond and c-BN from their hexagonal polymorphs. Previous studies have reported the synthesis of cubic B−C−N compounds under HPHT conditions. A cubic B−C−N phase has been successfully synthesized by Badzian at 14 GPa and 3300 K starting from the graphitic B−C−N, and Kakudate et al have claimed the formation of a cubic B−C−N substance by a shock-wave technique. Knittle et al have also reported the presence of cubic B−C−N both in the microcrystalline B−C−N compounds and the graphite-structured mixture of BN and C as starting materials, prepared at 30 GPa and 1500 K .…”
Section: Introductionmentioning
confidence: 99%